Blinded review of hippocampal neuropathology in sudden unexplained death in childhood reveals inconsistent observations and similarities to explained paediatric deaths. (16th July 2021) - Leitner, Dominique F.; McGuone, Declan; William, Christopher; Faustin, Arline; Askenazi, Manor; Snuderl, Matija; Guzzetta, Melissa; Jarrell, Heather S.; Maloney, Katherine; Reichard, Ross; Smith, Colin; Weedn, Victor; et al.
Abstract: Aims: Hippocampal findings are implicated in the pathogenesis of sudden unexplained death in childhood (SUDC), although some studies have identified similar findings in sudden explained death in childhood (SEDC) cases. We blindly reviewed hippocampal histology in SUDC and SEDC controls. Methods: Hippocampal haematoxylin and eosin (H&E) slides ( n = 67; 36 SUDC, 31 controls) from clinical and forensic collaborators were evaluated by nine blinded reviewers: three board‐certified forensic pathologists, three neuropathologists and three dual‐certified neuropathologists/forensic pathologists. Results: Among nine reviewers, about 50% of hippocampal sections were rated as abnormal (52.5% SUDC, 53.0% controls), with no difference by cause of death (COD) ( p = 0.16) or febrile seizure history ( p = 0.90). There was little agreement among nine reviewers on whether a slide was within normal range (Fleiss' κ = 0.014, p = 0.47). Within reviewer groups, there were no findings more frequent in SUDC compared with controls, with variability in pyramidal neuron and dentate gyrus findings. Across reviewer groups, there was concordance for bilamination and granule cell loss. Neither SUDC (51.2%) nor control (55.9%) slides were considered contributory to determining COD ( p = 0.41). Conclusions: The lack of an association of hippocampal findings in SUDC and controls, as well as inconsistency of observations by multiple blinded reviewers, indicates discrepancy with previous studies and an inability to reliably identify hippocampal maldevelopment associated with sudden death (HMASD). These findings underscore a need for larger studies to standardise evaluation of hippocampal findings, identifying the range of normal variation and changes unrelated to SUDC or febrile seizures. Molecular studies may help identify novel immunohistological markers that inform on COD. Abstract : We reviewed SUDC hippocampal histology to determine whether previous reports of common findings in this region could be identified when compared with controls with explained COD. We report lack in association of hippocampal findings in 36 SUDC and 31 controls, no association with febrile seizures and inconsistency of observations by nine blinded reviewers (three forensic pathologists, three neuropathologists and three dual neuropathologists/forensic pathologists). Larger studies are needed to standardise hippocampal findings, identifying the range of normal variation and pathology.